Regional state aid control in Europe: A legal and economic assessment - Hans W. Friederiszick; Massimo Merola (European School of Management and Technology (ESMT), 2015)
This paper provides a legal and economic analysis of the European rules for regional State aid according to Article 107 (1) and (3) TFEU. It summarizes the historical evolution and the trends of regional aid rules and describes the economic rationale behind them. The main principles are discussed with reference to recent academic research, leading cases and the State Aid Modernization initiative ("SAM"). The current rules for the assessment of compatibility as laid down in the General Block Exemption and the Regional Aid Guidelines 2014 are critically reviewed in light of these principles.
urn:nbn:de:101:1-201512023388
Keywords: 650; regional development policy; investment subsidies; European State aid control; competition law & economics